2020
DOI: 10.3390/w12061657
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ceramic Water Filter Clay Selection Criteria

Abstract: Ceramic water filters (CWFs) are point-of-use drinking water treatment systems that are manufactured and used in under-served communities around the world. The clayey material (CM) used to manufacture CWFs is a locally sourced mixture of clay, sand, slit and amorphous material (usually dug near the CWF factory). CM varies in composition and purity depending on the geographical location and geological setting. In this study, a set of 13 CM samples collected from around the world were analyzed using grain size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Venis and Basu (2021) indicated that CPFs were used at about 700,000 locations in 2014 and serving 4 million people (van der Lann et al, 2014). Numerous other articles exist (Bloem et al, 2010;Kallman, 2013;Annan et al, 2018;Bulta and Michael, 2019;Shepard et al, 2020;Pérez-Vidal et al, 2021;Venis and Basu, 2021) indicating adjustments such as use of different raw material ratios as sacrificial inputs in the making of the ceramic filter (e.g., rice husk, coffee grounds, and sawdust). Less frequently, other materials have also been used including peanut husk (Chaukura et al, 2020a) and coconut husk (Rivera-Sanchez, 2020) on the performance of CPFs.…”
Section: Basic Issues Of Failure Of Available Low-tech Water Treatmen...mentioning
confidence: 99%
“…Venis and Basu (2021) indicated that CPFs were used at about 700,000 locations in 2014 and serving 4 million people (van der Lann et al, 2014). Numerous other articles exist (Bloem et al, 2010;Kallman, 2013;Annan et al, 2018;Bulta and Michael, 2019;Shepard et al, 2020;Pérez-Vidal et al, 2021;Venis and Basu, 2021) indicating adjustments such as use of different raw material ratios as sacrificial inputs in the making of the ceramic filter (e.g., rice husk, coffee grounds, and sawdust). Less frequently, other materials have also been used including peanut husk (Chaukura et al, 2020a) and coconut husk (Rivera-Sanchez, 2020) on the performance of CPFs.…”
Section: Basic Issues Of Failure Of Available Low-tech Water Treatmen...mentioning
confidence: 99%
“…Numerous others (e.g. Bulta &Michael, 2019;Kallman, 2013;Bloem et al, 2009;Pérez-Vidal et al, 2021;Annan et al, 2018;Venis and Basu, 2021;Shepard et al 2020;Venis and Basu, 2021). Many research articles exist indicating adjustments such as use of different raw material ratios as sacrificial inputs in the making of the ceramic filter (e.g.…”
Section: Some Of the Basic Issues Of Failure Of Available Low-tech Wa...mentioning
confidence: 99%
“…A CWF is a porous filter made from clay and sieve materials. CWFs are made from a combination of clay, water, and combustible materials like sawdust or rice husks . The sieve materials could be sand, sawdust, or other burnout materials .…”
Section: Introductionmentioning
confidence: 99%